Antifungal Assessment of Chemical and Biological Control Agents Against Major Seed-Borne Pathogens of Sesame (Journal of Agriculture and Biology, 2026)
Sesame (Sesamum indicum L.) is an important oilseed crop renowned for its nutritional, economic, and medicinal significance, particularly in tropical and subtropical regions. The aim of this research is to investigate the seed-borne fungal pathogens associated with sesame and evaluate the effectiveness of treatments under in vitro and in vivo conditions. The pathogens associated with the seeds were isolated by placing the infected seeds on the potato dextrose agar (PDA) media. The most frequent pathogens associated with seeds were Aspergillus niger and Curvularia lunata. These pathogens were later purified by using the hyphal tip and single-spore purification technique. Seed-associated pathogens were managed in vitro and in vivo with the help of chemical fungicides and bacterial BCAs. Statistical analyses were conducted using analysis of variance (ANOVA), a completely randomized design (CRD), and a randomized completely blocked design (RCBD). Under in vitro conditions, Amistar Top (Azoxystrobin + Difenoconazole) at 150 ppm proved efficient against C. lunata inhibited their growth up to 85% and Hombre (Imidacloprid + Tebuconazole) at 150 ppm against A. niger showed significant result up to 86% respectively. Agrobacterium fabrum showed significant antagonistic activity against both C. lunata and A. niger, Inhibited their growth up to 82% and 67% respectively. Under in vivo conditions, variety TH-6 was treated with most effective treatments identified in laboratory experiments. Amistar Top and Hombre, applied at 150 ppm under field conditions, resulted in 30% disease incidence against C. lunata and 32% against A. niger in comparison to untreated control with 80% disease incidence, respectively. A. fabrum applied against both pathogens, recorded 42% disease incidence against C. lunata and 45% against A. niger. These disease management strategies emphasize the use of standard concentrations and selective treatments for better results.